1. Producer gas from indigenous solid fuels 2. Conversion of oil-fired boilers to utilize solid fuel - Cruz, Ibarra E. (Philippine Engineering Journal)
The following two papers by Dr. Ibarra E. Cruz describe experimental results of solid fuel gasification research conducted in the M.E. Department in the early seventies. This was a time when the effects of the Arab oil embargo and the energy crisis jolted the country into a frantic search for alternative and local sources of energy to attain some measure of energy security. In the first paper, gasification of coconut shells, coir dust, and ipil ipil wood chips were conducted using a gas producer design that allowed operation either as a downdraft or updraft reactor. This design feature was conveniently used to compare the performance of the updraft and downdraft gas producer in terms of operating characteristics and gas quality produced, specifically CO, CO2, and H2 content. Three gas producer sizes ("small", "medium", "big") of increasing grate area and fuel feed rate were built and tested. Results of the experiments indicate the updraft reactor yielded higher CO and lower CO2 than the downdraft reactor. Higher H2 content in the gas was obtained with the downdraft reactor. No operational difficulties from clinker formation were experienced with the small and medium size reactors. This was attributed to gasification rates being equal to or less than 40 (lbs/hr) ft2. grate area. The big gas producer operated as an upward reactor, with gasification rates of about 80 (lbs/hr) ft2. grate area, encountered heavy formation of dense and hard clinker on the grate which blocked air passage and eventually stopped operation. Saturation of the air supply with water during updraft reactor operation produced lighter clinker which was broken by occasional poking of the grate bed with a rod thus allowing uninterrupted gas production. It is believed that problems from clinker formation could be lessened by operating the gas producer as a downdraft reactor. The second paper presents results of an attempt to convert a 100 hp oil fired steam boiler to gaseous fuel produced from coconut shells. An updraft gas producer of 10-ft2. grate area, piping and two gas burners were built and fabricated for the purpose. Steam generated was used to drive a high speed (1200 rpm), 3 cylinder steam engine coupled to a 50 kW electric generator with a water rheostat load. An initial run at 40 (lbs/hr)ft.2 grate area gasification rate, air blast above the grate, and using one blower encountered intense burning and clinker formation at the air inlets eventually blocking air passage. High pressure drop between the gasifier and boiler furnace piping resulted to a low gas delivery and thus, a low power output (7 kW). During a second run, use of two blowers connected in series together with a increased diameter (from 4" to 6") of the gas pipe to the boiler enabled higher power output from the boiler genset. The air blast was also introduced below the grate in this run which caused clinker formation on the grate prematurely interrupting gasifier operation. A third run introduced water with the air blast under the grate resulting into a friable clinker formation. Together with vigorous manual poking of the bed during fuel charging, clinker formation became manageable enabling higher gasification rates (about 84 lbs/hr/ft.2 grate area) and a steady steam engine generator load of 35 kW. Overall, the use of gasification was partially successful. Clinker formation presents a serious problem at high gasification rates without addition of water steam in their air blast.